The relationship between social networking websites usage and student’s academic performance / Farah Nadhirah Zainal, Nor Hamizah Che Wail, Siti Hapsah Ahmad and Sur Ain Naquiah Nik - Zainal, Farah Nadhirah; Che Wail, Nor Hamizah; Ahmad, Siti Hapsah; Nik, Sur Ain Naquiah (2011)
Social networking website is one of the social media Internet-based services includes Facebook, MySpace, Orkut, Cyworld, Bebo and other social networking sites that allow individuals to present themselves to other users using a variety of formats, including text and video. All of these sites allow the users to exchange news and discuss issues, chatting, update status, discussing, find friends as well as share the information with each other. In Malaysia, social networking becomes a phenomenon among the citizens regardless of their age, race, occupation and living area and students are the most users of social networking sites. This research is focus on the relationship between the social networking websites and students academic performance. This study was conducted in order to identify either there is a relationship or not between these two variables. The ob jective of this study is to investigate the usage of social networking among UiTMT university students A set of questionnaires have been distributed in a ways to find the result and from the data collected, we know the actual usage of social networking website among the UiTMT students. Respondents for this research are students from part six in four faculties which are Electrical Engineering, Office Management, Hotel Management and Business Management of the UiTM Terengganu. The data received has been analyzed by using the mean, standard deviation, percentage, frequency and Pearson’s correlation. From this analyzing technique, actual results have been received and based on the Pearson correlation analysis, we can conclude that there is a relationship between social networking website and students academic performance Overall, the findings of the research help the student to beware about the usage of the social networking website as well as know there is a relationship exists between the usage of social networking website and students academic performance.